y=.5x-4

Simple and best practice solution for y=.5x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=.5x-4 equation:


Simplifying
y = 0.5x + -4

Reorder the terms:
y = -4 + 0.5x

Solving
y = -4 + 0.5x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -4 + 0.5x

See similar equations:

| 14=2b | | y=-2.2x-5 | | 6x-8=2(x-4) | | 8xy-2xy= | | p+4-5=3p-8-7p | | 5x-8x+2x= | | (-6)-(2)-(-3)= | | 8q=38 | | (-8)+(-2)+(-5)= | | 4x+3y=4 | | X^2+14y+13=0 | | r^2-6tw+3wr-2tr= | | (-5)-(10)= | | ln(x-2)=1 | | (-20)-(-20)= | | 7x-y=7 | | 5x-4x+3=6x-4-2x | | 10a=40 | | (-52)-(-38)= | | 13k+4=4k-3 | | 4z=16 | | 2(8-2p)+4(p+7)=44 | | X^2-6x=18 | | 9x^2-3x-3xy-y=0 | | 3p-2=5p+5 | | 8p^2+128p-1140=0 | | -3-4n-7n=-14 | | 6m-3=2m+8 | | 6(7-4n)=186 | | 27x^3y^6-a^9c^12=0 | | 39=3y | | -(6+6m)-7(m+3)=64 |

Equations solver categories